Effect of Online Behavioral Advertising Implementation on Attitude Toward Ad and Purchase Intention in Indonesian E-Marketplace - Tamas Fachryto; Adrian Achyar (Faculty of Economics, Universitas Sriwijaya, 2018)
Internet user increase certainly support e-commerce growth. So some e-commerce companies perform online behavioral advertising (OBA) to get consumers as much as possible. The current study uses retargeted ads as a kind of the latest OBA which most of e-marketplaces in Indonesia implement the ads. Survey in the form of questionnaire from 261 respondents. The respondents were showed by author the example of e-marketplace’s online behavioral advertising picture and video first before answering the questionnaire. It is intended to recall respondents that they have ever seen ads similar to OBA. The result of this study revealed that OBA threatened consumer privacy, so led to cognitive and affective reactance. Perceived ad intrusiveness also had positive effect on perceived threat. OBA led negative attitude toward the ad and finally negative consumer purchase intention toward product which displayed on OBA.